CanDiD: A Framework for Linking Executive Function and Education - Kamkar, Niki H.; Morton, J. B. (Frontiers in Psychology, 2017)
The close association between executive functions (EFs) and educational achievement has led to the idea that targeted EF training might facilitate learning and goal-directed behavior in the classroom. The evidence that training interventions have long-lasting and transferable effects is however decidedly mixed (Melby-Lervåg and Hulme, 2013; Simons et al., 2016). The goal of the current paper is to propose a new CanDiD framework for re-thinking EF and its links to education. Based on findings from basic EF research, the proposed CanDiD framework highlights dynamic and contextual influences on EF and emphasizes the importance of development and individual differences for understanding these effects. Implications for remedial interventions and curriculum design are discussed.